Concurrent cutaneous papilloma and vaginal fibroepithelial polyp in an adult female dog - Ola, Olawale Olawumi; Jarikre, Theophilus Aghogho; Tijani, Monsuru Oladunjoye; Olaifa, Olanrewaju Samuel; Adekunle, Usman Abdulrauf; Ohore, Obokparo Godspower; Alaka, Olugbenga Olayinka; Omosekeji, Linda Chinyere; Onoja, Moyinoluwa Julianah; Bolaji, Oluwadarasimi Faith; Oyeyemi, Matthew Olugbenga; Fagbohun, Olusegun Adesina; Eyarefe, Oghenemega David (Universitas Airlangga, 2025)
Simultaneous occurrence of cutaneous papilloma and vaginal fibroepithelial polyp in old dogs is rare, making such cases clinically and academically significant. An eight-year-old female Boerboel presented with a one-year history of non-pruritic, wart-like skin lesions and a large vulvar mass observed on the day of presentation. Clinical examination, fine-needle aspiration, surgical excision, and histopathological analysis were performed to establish the diagnosis. The vulvar mass measured 16 × 10 × 8 cm, was firm, hyperemic, and smooth, with focal necrosis and hemorrhage. Cutaneous lesions were small, irregular, and cauliflower-like, located on the flank and hind digits. The client had initially misinterpreted the associated bloody vaginal discharge as estrus. Fine-needle aspirates from the vulvar mass showed predominantly cornified epithelial cells. Histopathological examination confirmed the skin lesions as cutaneous papillomas, characterized by hyperplastic stratified squamous epithelium with orthokeratotic hyperkeratosis, and acanthosis. The vaginal mass was diagnosed as a fibroepithelial polyp composed of a hypocellular stroma of bland spindle cells, non-keratinized squamous epithelium, and dense neutrophilic infiltration with necrotic debris. This case adds to the sparse body of knowledge on concurrent cutaneous and reproductive tract lesions in dogs. It emphasizes the critical role of thorough clinical evaluation and histopathological confirmation in distinguishing lesions that may appear related but are distinct. Early surgical intervention is essential for effective management and a favorable prognosis, and systematic documentation of such cases enhances understanding of unusual presentations in veterinary practice.